If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4c + -2 = 18 Reorder the terms: -2 + 4c = 18 Solving -2 + 4c = 18 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 4c = 18 + 2 Combine like terms: -2 + 2 = 0 0 + 4c = 18 + 2 4c = 18 + 2 Combine like terms: 18 + 2 = 20 4c = 20 Divide each side by '4'. c = 5 Simplifying c = 5
| 2x+12=-3x+5 | | Y=9/8x | | 2(z+-13)=-12 | | 5xa-12xa=-35 | | X+8=28+X | | 4y+8=3y | | 6q+2r-q+7r= | | -9d-4d=15 | | 129+191=n | | 10h-5h-4=6 | | 5a-12a=-35 | | 3x(3x-2)-4x(3x+4)= | | 13x+26=6x+180 | | 8q-5q= | | 9c-8=1 | | 2x-x=24-2x | | 20d-18d=2 | | 9y-6=-456 | | 7g=4 | | 17d-15d=20 | | 4n-6=94 | | x/4=3/4 | | 5x(2x+3)-2x(2x-1)= | | 2x-1/5=1 | | h=-16t^2+60t+2 | | 3a+6b+2a-5b= | | 2/7(x-4)=2 | | 2.20=12.15 | | 7x+2y-5x-5y= | | (5-2x)*(4-x)-2x*(x+6)=1-x | | 7(3x-5y)-4(4x-5y)= | | 6y+11=4 |